2012
DOI: 10.1111/cas.12048
|View full text |Cite
|
Sign up to set email alerts
|

Early response and local control of stage I non‐small‐cell lung cancer after stereotactic radiotherapy: difference by histology

Abstract: To investigate the possible influences of various factors on tumor response to radiation, regression speeds and long-term local control rates of primary adenocarcinoma and squamous cell carcinoma of the lung after stereotactic body radiotherapy were evaluated. Ninety-one patients (65 men and 26 women) with a median age of 76 years were serially examined using computed tomography at 2, 4 and 6 months after treatment. Tumor histology was adenocarcinoma in 62 patients and squamous cell carcinoma in 29 patients. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Decrease in tumor volume of 10% or more was observed in 3 (6%) patients. Previous studies indicated that squamous cell carcinomas regress faster than adenocarcinomas after Gamma Knife treatment or lung SBRT [ 17 , 18 ], but in the present study, 2 of the 3 tumors were adenocarcinomas while one was a squamous cell carcinoma. Rapid decrease of tumor volume during the course of SBRT may be due to apoptosis of the tumor cells [ 19 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Decrease in tumor volume of 10% or more was observed in 3 (6%) patients. Previous studies indicated that squamous cell carcinomas regress faster than adenocarcinomas after Gamma Knife treatment or lung SBRT [ 17 , 18 ], but in the present study, 2 of the 3 tumors were adenocarcinomas while one was a squamous cell carcinoma. Rapid decrease of tumor volume during the course of SBRT may be due to apoptosis of the tumor cells [ 19 ].…”
Section: Discussioncontrasting
confidence: 76%
“…44 However, a recent prospective study examining the difference in SBRT response between the two histologies showed that although tumor shrinkage was faster for SCC than adenocarcinomas at 2 and 4 months, there was no difference in the mean tumor size at 6 months or in the 3-year LC. 45 Our results are likely biased by the small sample size and the low event rate; caution is therefore exercised in extrapolating any definitive conclusions from the data.…”
mentioning
confidence: 78%
“…It is still not commonly agreed whether tumor histology is related to clinical outcomes in NSCLC treated with SBRT. Some studies have reported an absence of statistically significant differences in the survival or recurrence rates of adenocarcinomas and SCC [32, 33]. Matsuo et al analyzed 101 patients with histologically confirmed stage I NSCLC who underwent SBRT [34], and reported that females had a significantly better prognosis than males and that histology was less significant.…”
Section: Discussionmentioning
confidence: 99%